2018
DOI: 10.1590/0102-311x00165817
|View full text |Cite
|
Sign up to set email alerts
|

Estado nutricional e condições ambientais e de saúde de crianças Pataxó, Minas Gerais, Brasil

Abstract: To describe the nutritional status and the environmental and health conditions of the Pataxó children from five villages of Minas Gerais State, Brazil. Among the under 10 years old, weight and height/length were classified according to the growth references of World Health Organization. Questionnaires evaluating environmental conditions of the households and health conditions of under 5 years old were based in the First National Survey of Indigenous People's Health and Nutrition. Among the 70 children evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 4 publications
0
4
0
2
Order By: Relevance
“…The precarious scenario experienced in the villages results in other health challenges, which can be observed in the high rates of illness such as diarrhea, influenza, and Malaria, high rates of hospital admissions, and the high number of abortions and fetal deaths, revealing gaps in health services. Additionally, the lack of sanitation plays a significant role in nutritional deviations and in the high rates of anemia recorded in children under five years old [120][121][122][123].…”
Section: Discussionmentioning
confidence: 99%
“…The precarious scenario experienced in the villages results in other health challenges, which can be observed in the high rates of illness such as diarrhea, influenza, and Malaria, high rates of hospital admissions, and the high number of abortions and fetal deaths, revealing gaps in health services. Additionally, the lack of sanitation plays a significant role in nutritional deviations and in the high rates of anemia recorded in children under five years old [120][121][122][123].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies around the world, mostly carried out in Latina America, that investigated the determinants of Indigenous children's health indicated that living conditions, location in remote regions, limited access to public health policies, sanitation, and housing conditions, and schooling are shown to be a relevant context for the high frequencies of infectious diseases. 17 , 19 , 20 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 Thus, evidence indicates that housing conditions, access to water & sanitation, and socioeconomic characteristics have implications for health profile, especially in children.…”
Section: Discussionmentioning
confidence: 99%
“…Segundo a Sociedade Brasileira de Pediatria, as causas de diarreia na criança são inúmeras, no entanto, as principais são divididas em grupos, como exemplo: 1) Infecciosas bacterianas: Salmonella, Shigella, Campylobacter, Yersinia, Escherichia coli; 2) Infecciosas virais: Rotavírus, Norovírus, Adenovírus; 3) Infecciosas por protozoários: ameba, Giárdia lamblia, Cryptosporidium16. Dessa forma, assegurar condições de higiene adequada é um fator determinante para diminuir os casos de diarreia nessas crianças (SANTOS AP, et al, 2018;BRASIL, 2019).…”
Section: Discussionunclassified